2015
DOI: 10.1111/jdi.12372
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 diabetes patients have lower strength in femoral bone determined by quantitative computed tomography: A cross‐sectional study

Abstract: Aims/IntroductionPrevious studies have reported osteoporosis measured by dual-energy X-ray absorptiometry in younger patients with type 1 diabetes. Limitations of 2-D imaging, however, limit the precision of dual-energy X-ray absorptiometry for the measurement of bone mineral density and bone strength.Materials and MethodsThree-dimensional quantitative computed tomography was used to calculate volumetric-bone mineral density (vBMD) and strength in femoral bone subfractions. A total of 17 male type 1 diabetes p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 43 publications
(78 reference statements)
1
7
0
Order By: Relevance
“…Previous evidence regarding cortical microarchitecture in Asian T1D patients is lacking. Our results were consistent with those from the only previous study to demonstrate lower cortical CSA and thickness in young and middle-aged Japanese T1D adults [ 18 ]. Two studies conducted in a Western population with older age and longer disease duration also found similar results.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previous evidence regarding cortical microarchitecture in Asian T1D patients is lacking. Our results were consistent with those from the only previous study to demonstrate lower cortical CSA and thickness in young and middle-aged Japanese T1D adults [ 18 ]. Two studies conducted in a Western population with older age and longer disease duration also found similar results.…”
Section: Discussionsupporting
confidence: 93%
“…However, only one of these studies has focused on an Asian population, and that study had a very small sample size. In that cross-sectional study conducted among Japanese subjects, 17 young or middle-aged T1D patients were found to have significantly lower cortical thickness and cortical CSA in the femoral intertrochanter than 18 healthy control subjects [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have addressed skeletal impairment in men with T1D, and these studies suggest that men experience a more marked bone affection than their female counterparts 14,15 . Men with T1D also have increased femoral neck fragility and decreased femoral strength assessed by QCT compared to controls 16,17 .The main objective of this study was therefore to assess bone quality by measurement of TBS and BMSi by IMI in men with T1D compared to healthy age-matched men. Moreover, we wanted to examine BMD, bone turnover, serum pentosidine, and the associations of TBS and BMSi with BMD, glycated hemoglobin (HbA 1c ), duration of disease, and daily insulin dosage.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the previous reports may have underestimated the effect of denosumab discontinuation. With QCT, bone strength can be evaluated and trabecular bone and cortical bone can be assessed separately in three dimensions, without the interference of the surrounding osteophytes 9,15,16. The magnitude of bone loss was greater in the femoral bone than in the LS, and the FN-BMD returned to the average baseline value.…”
Section: Discussionmentioning
confidence: 99%